PERAN TELEPHONE OPERATOR DAN BELLDRIVER PADA FRONT OFFICE DEPARTMENT DI HOTEL IBIS MALIOBORO YOGYAKARTA - , ROBIN IBNU JAFAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Telephone Operator and Belldriver are two parts which be related and they have important task and role especially in front office department so that to be a tip of spear in a hotel. So in this Last Task will be explain about their task and role which called important component of hotel. Needed a recent survey to understanding those thing so that the explanattion will be write down doesnât lost of meaning. In this case on the job training and recent interview by profesional staff in Hotel Ibis Malioboro Yogyakarta is better method to used. This research produce many profit which very important for front office department, the one of all is helping front office department to keep hotel image stay good and handle any complain.